Use Ukrainian songs of folklore in a technique of development tunes of feeling of the future teachers - R.O. Lyubar (Academy of Cognitive and Natural Sciences, 2009)
In clause the questions of the Ukrainian folk music, efficiency of their use in a technique of development of musical hearing of the future teachers of music are considered.